Komodifikasi Sensasi: Analisis Strategi Digital Branding dan Visual Marketing Bakso Rusuk Joss dalam Menciptakan Viralitas di Media Sosial - Supriyadi Supriyadi (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study analyzes the digital branding strategy and virality mechanisms of Bakso Rusuk Joss (BRJ), a viral culinary MSME in Indonesia. Using a qualitative netnographic approach on TikTok and Instagram, supported by interviews and documentation, the study examines online interactions, visual content, and user-generated content (UGC). The findings show that BRJ’s success is driven by three key factors: (1) visual-led product innovation (e.g., Bakso Lava) that encourages UGC production; (2) experiential marketing that transforms eating into a shareable visual and emotional experience; and (3) influencer-driven exposure that triggers Fear of Missing Out (FOMO). These strategies position consumers as active co-creators who amplify brand visibility organically. The study concludes that BRJ commodifies sensation, where product value lies not only in taste but in its potential to generate digital content and attention. This research provides insights for culinary MSMEs in designing effective marketing strategies within the attention economy.